ChemInform Abstract: Regioselective Functionalization of the Oxazole Scaffold Using TMP‐Bases of Mg and Zn. Issue 25 (24th June 2014) - Haas, Diana; Mosrin, Marc; Knochel, Paul
Abstract This new and general method allows the construction of oxazole derivatives with up to three different substituents.